A new brachypterous leafhopper of the tribe Malmaemichungiini (Hemiptera: Cicadellidae: Bathysmatophorinae), representing the first record of the tribe from China - Wei, Cong; Zhang, Yalin; Dietrich, Christopher H. (Zootaxa, 2010)
The rare brachypterous leafhopper genus Malmaemichungia Kwon is revised with the description and illustration of a new species, Malmaemichungia qinlingensis sp. nov., from the Qinling Mountains, central China. The new species represents a substantial extension of the known range of the tribe Malmaemichungiini, all other species of which are recorded from South Korea. The taxonomic position and biogeography and habitats of Malmaemichungiini and the closely related Bathysmatophorini are discussed. Bathysmatophorinae is here treated as a separate subfamily for the first time (new status) and includes the nominotypical tribe and Malmaemichungiini.